EVALUASI PENGELOLAAN SAMPAH DI WILAYAH PESISIR KABUPATEN KEPULAUAN ANAMBAS - Rita Puspitasari Heryani; Ani Suryanti; Nevrita Nevrita (Jurnal Ilmu Lingkungan, 2021)
Garbage is still a crucial problem that can pollute and damage the environment in several areas in Indonesia. Anambas Islands Regency which is a coastal area also has the potential to experience marine pollution, so that waste management is needed early on. However, until now, waste management has not become a priority for the attention of the community and local governments. To find out how the condition of the waste management system in general, a study of waste management in the Anambas Islands Regency was carried out. The main factors causing the less than optimal waste management in the Anambas Islands Regency are the lack of infrastructure, the low understanding of the community in managing waste, and the weak application of the Anambas Islands Regency Perda. Therefore, in order to optimize waste management, support in the form of adequate facilities and also the application of a Perda which is strictly implemented from the local government of the Anambas Islands Regency is needed.